2018
DOI: 10.1051/kmae/2018018
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of overland dispersal in the invasive crayfish Faxonius immunis (Hagen) at the Upper Rhine River area

Abstract: The non-indigenous crayfish Faxonius immunis (Hagen) is the dominant crayfish species at the Upper Rhine River system since his detection in 1993. As an invasive alien species, it is one of the biggest threats to aquatic biodiversity in the area. By dispersing over land, the species has a high potential to colonize small ponds created for threatened amphibians and dragonflies. Shortly after invasion, the fast growing population of F. immunis is changing the habitat drastically. In June 2016, our team started a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…P. clarkii is considered a "tertiary burrower" (Hobbs, 1981), spending most of its life in open waters and only retreating in burrows to avoid predators and dehydration or when breeding (Gherardi, 2001). On the other hand, a terrestrial behavior was reported by Huner (2002), Chucholl (2011) and Abdel-Kader (2016) who observed P. clarkii migrating overland to explore new habitats in response to poor water quality (McCarthy et al, 2014) or for dispersal among waterways (Morgan, 1991;Furse et al, 2004;Herrmann et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…P. clarkii is considered a "tertiary burrower" (Hobbs, 1981), spending most of its life in open waters and only retreating in burrows to avoid predators and dehydration or when breeding (Gherardi, 2001). On the other hand, a terrestrial behavior was reported by Huner (2002), Chucholl (2011) and Abdel-Kader (2016) who observed P. clarkii migrating overland to explore new habitats in response to poor water quality (McCarthy et al, 2014) or for dispersal among waterways (Morgan, 1991;Furse et al, 2004;Herrmann et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…The relations between F. immunis density and a-diversity outline the relevance of ongoing crayfish management in areas where rare macroinvertebrate species occur. With its strongly r-selected life history (Tack 1941;Chucholl 2012) and its ability to migrate over land (Herrmann et al 2018a), F. immunis will be a growing threat for macroinvertebrate communities and ecosystem services along waterbodies invaded by this crayfish species.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of F. immunis is not limited to the main river and its oxbows, and it also disperses through interconnected watercourses and ditches (Chucholl 2012;Martens 2016). The species is able to disperse over land and populate isolated ponds next to its habitat of origin at any time of the year (Herrmann et al 2018a). This also happens for temporary ponds created for nature conservation, where the crayfish can be a threat to animals like the lilypad whiteface Leucorrhina caudalis or the European tree frog Hyla arborea, which are protected under the European Bird's and Habitats Directive (European Economic Community 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These locations from Poland's biggest cities are characterised by higher risk of possible actions of irresponsible aquarists releasing unwanted pets (Perdikaris et al, 2012;Maciaszek et al, 2019a and cited papers therein) that are known from local artificial ponds (Maciaszek et al, 2019b;Maciaszek et al, 2019c) as well as natural reservoirs (Maciaszek and Sosnowski, 2019). According to relative small distance to open waters of Vistula River and ability of P. clarkii to traverse the land (Herrmann et al, 2018), both sites could become a potential source of further invasion (Chucholl, 2015;Patoka et al, 2016;Lipták et al, 2017), especially that passive transportation of this species by aquatic birds has been also documented (Anastácio et al, 2014).…”
Section: Discussionmentioning
confidence: 99%